Correction to: Comparison of three different methods of internal sinus lifting for elevation heights of 7 mm: an ex vivo study - Aghiad Yassin Alsabbagh; Mohammed Monzer Alsabbagh; Batol Darjazini Nahas; Salam Rajih (SpringerOpen, 2020)
An amendment to this paper has been published and can be accessed via the original article.